H1N1 influenza vaccination in HIV-infected women on effective antiretroviral treatment did not induce measurable antigen-driven proliferation of the HIV-1 proviral reservoir. Issue 1 (December 2017) - Wagner, Thor; Huang, Hannah; Salyer, Christen; Richardson, Kelly; Weinberg, Adriana; Nachman, Sharon; Frenkel, Lisa
Abstract Objectives Antigen-induced activation and proliferation of HIV-1-infected cells is hypothesized to be a mechanism of HIV persistence during antiretroviral therapy. The objective of this study was to determine if proliferation of H1N1-specific HIV-infected cells could be detected following H1N1 vaccination. Methods This study utilized cryopreserved PBMC from a previously conducted trial of H1N1 vaccination in HIV-infected pregnant women. HIV-1 DNA concentrations and 437 HIV-1 C2V5env DNA sequences were analyzed from ten pregnant women on effective antiretroviral therapy, before and 21 days after H1N1 influenza vaccination. Results HIV-1 DNA concentration did not change after vaccination (median pre- vs. post-vaccination: 95.77 vs. 41.28 copies/million PBMC, p = .37). Analyses of sequences did not detect evidence of HIV replication or proliferation of infected cells. Conclusions Antigenic stimulation during effective ART did not have a detectable effect on the genetic makeup of the HIV-1 DNA reservoir. Longitudinal comparison of the amount and integration sites of HIV-1 in antigen-specific cells to chronic infections (such as herpesviruses) may be needed to definitively evaluate whether antigenic stimulation induces proliferation of HIV-1 infected cells.